Testing the role of online group-based supervision for local humanitarian workers following a crisis: A mixed-methods longitudinal study. - Gülşah Kurt; Fatema Almeamari; Hafsa El-Dardery; Aya Kardouh; Scarlett Wong; Michael McGrath; Louis Klein; Ammar Beetar; Salah Lekkeh; Ahmed El-Vecih; Wael Yasaki; Ceren Acarturk; et al. (PLOS Global Public Health)
The 2023 Türkiye-Syria earthquakes caused widespread destruction, leaving millions without access to basic needs and services. Caring for Carers (C4C), an online group-based supervision program for Syrian mental health workers, started three months prior to the earthquakes. This study examined the role of this program in supporting the mental and occupational health of the participants following this crisis. A mixed-method longitudinal design was employed with Syrian mental health workers in Türkiye and Northwest Syria (N = 55, 45.5% female), including 16 months of survey data on psychological distress (Kessler-6) and compassion satisfaction (ProQOL), semi-structured interviews with supervisors (N = 10), and video recordings of supervision sessions (N = 9). A piecewise mixed-effects model within a Bayesian Hierarchical framework was used to assess changes in outcomes across three periods: the active control period (7 months), pre-earthquake supervision period (3 months), and post-earthquake supervision period (6 months). The thematic analysis was used to analyze the qualitative data from the interviews and supervision sessions. Quantitative findings showed a significant reduction in psychological distress and an increase in compassion satisfaction during the post-earthquake supervision period (b = -0.18, error = 0.06, CrI = -0.29, -0.07, b = 0.26, error = 0.04, CrI = 0.18, 0.35, respectively). These changes were significantly different from the active control period (b = 0.21, error = 0.05, CrI = 0.11, 0.31, b = -0.37, error = 0.04, CrI = -0.45, -0.28, respectively) while no significant differences were observed between the active control and pre-earthquake supervision periods. Thematic analysis identified five features of supervision as a safe space and two functions as a source of emotional and practical support after the earthquakes. Overall, these findings provide evidence for both the protective and promotive role of supervision among Syrian mental health workers, highlighting the key mechanisms through which it may foster resilience and strength in humanitarian settings.